2020
DOI: 10.1101/2020.08.26.20182584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multipurpose machine learning approach to predict COVID-19 negative prognosis in São Paulo, Brazil

Abstract: Introduction The new coronavirus disease (COVID-19) is a challenge for clinical decision-making and the effective allocation of healthcare resources. An accurate prognostic assessment is necessary to improve survival of patients, especially in developing countries. This study proposes to predict the risk of developing critical conditions in COVID-19 patients by training multipurpose algorithms. Methods A total of 1,040 patients with a positive RT-PCR diagnosis for COVID-19 from a large hospital from Sao Paulo,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The algorithms were selected based on their demonstrated utility in healthcare prediction models [ 54–57 ] and evaluated using Scikit-Learn [ 58 ]. Random Forest, which has been commonly used for predicting hospitalizations [ 59 ] and ICU admission [ 60–62 ], is a decision tree-based model that can run multiple parallel trees. This technique averages predictions of all trees generated, allowing for a reduction of overfitting [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…The algorithms were selected based on their demonstrated utility in healthcare prediction models [ 54–57 ] and evaluated using Scikit-Learn [ 58 ]. Random Forest, which has been commonly used for predicting hospitalizations [ 59 ] and ICU admission [ 60–62 ], is a decision tree-based model that can run multiple parallel trees. This technique averages predictions of all trees generated, allowing for a reduction of overfitting [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on these results, the following calculations were performed: Digestible energy = Gross energy ingested − Gross energy of feces; and Metabolizable energy = digestible energy − gross energy lost in urine and gases. Meanwhile, gas energy was estimated as 8% of the total energy [35].…”
Section: Energy Balancementioning
confidence: 99%
“…We additionally report the predictive ability for mortality risk of the COVID-19 positive samples on the basis of the blood tests only, again with no additional expensive features [33][34][35]38,40,41,53,54 . Compared to previous studies 33,36,37,39 , our mortality models are trained on a large number of COVID-19 positive patients.…”
Section: Degrading Of Predictive Performance Over Timementioning
confidence: 99%
“…COVID-19 and the patient's prognosis can be predicted from chest CT-scans, X-rays [11][12][13][14] or sound recordings of coughs or breathing [15][16][17] . Furthermore, it has been shown that ML models based on blood tests are capable of detecting COVID-19 infection [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and predicting other outcomes, such as survival or admission to an intensive care unit [33][34][35][36][37][38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%